3q-(2-q)=2(2q-1)

Simple and best practice solution for 3q-(2-q)=2(2q-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3q-(2-q)=2(2q-1) equation:


Simplifying
3q + -1(2 + -1q) = 2(2q + -1)
3q + (2 * -1 + -1q * -1) = 2(2q + -1)
3q + (-2 + 1q) = 2(2q + -1)

Reorder the terms:
-2 + 3q + 1q = 2(2q + -1)

Combine like terms: 3q + 1q = 4q
-2 + 4q = 2(2q + -1)

Reorder the terms:
-2 + 4q = 2(-1 + 2q)
-2 + 4q = (-1 * 2 + 2q * 2)
-2 + 4q = (-2 + 4q)

Add '2' to each side of the equation.
-2 + 2 + 4q = -2 + 2 + 4q

Combine like terms: -2 + 2 = 0
0 + 4q = -2 + 2 + 4q
4q = -2 + 2 + 4q

Combine like terms: -2 + 2 = 0
4q = 0 + 4q
4q = 4q

Add '-4q' to each side of the equation.
4q + -4q = 4q + -4q

Combine like terms: 4q + -4q = 0
0 = 4q + -4q

Combine like terms: 4q + -4q = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 5x^4-9x^3-3x^2=0 | | 8k-2(k+7)=15-6k | | 100+12h=23h+h | | -18-a=-25 | | 8(x-1)=4(x+2)-x | | 4(5x+4)=20x+16 | | (13x)-4=(x-8) | | 3(x+1)-5=3x-3 | | 7-(4y-3)=4-5y | | .20x+.45(70)=45.5 | | x^2-6x-230=0 | | 1.3t+3(t+8.2)=375 | | 7t+8t=45 | | 2(2r+5)+1=5-3(3-r) | | 4(x-1)=2(x+2)-x | | 5v=-2v-3v | | -4y-12=3y+16 | | 9(x+8)=8(x-8)+x | | 5(1+4x)=2(3+10x) | | 2(n-4)=4(5-2n) | | 11x-21=8x | | w-4(w+2)=7-2w | | n^2-12+4n+11=76 | | 4a^2b^2-5ab= | | 13+7x=9+15x | | X*x+x+3=196+x-4 | | 50x^2=32 | | 4(3z-5)=8 | | 4(2/5)+k=-32/11 | | -1.32=3(1.5x-0.5) | | x^2-6y+y^2-7=0 | | 4.5x^2-9x+3.5=0 |

Equations solver categories